Tumor-Induced Cardiac Dysfunction: A Potential Role of ROS - Priyanka Karekar; Haley N. Jensen; Kathryn L. G. Russart; Devasena Ponnalagu; Sarah Seeley; Shridhar Sanghvi; Sakima A. Smith; Leah M. Pyter; Harpreet Singh; Shubha Gururaja Rao (Antioxidants, 2021)
Cancer and heart diseases are the two leading causes of mortality and morbidity worldwide. Many cancer patients undergo heart-related complications resulting in high incidences of mortality. It is generally hypothesized that cardiac dysfunction in cancer patients occurs due to cardiotoxicity induced by therapeutic agents, used to treat cancers and/or cancer-induced cachexia. However, it is not known if localized tumors or unregulated cell growth systemically affect heart function before treatment, and/or prior to the onset of cachexia, hence, making the heart vulnerable to structural or functional abnormalities in later stages of the disease. We incorporated complementary mouse and Drosophila models to establish if tumor induction indeed causes cardiac defects even before intervention with chemotherapy or onset of cachexia. We focused on one of the key pathways involved in irregular cell growth, the Hippo–Yorkie (Yki), pathway. We used overexpression of the transcriptional co-activator of the Yki signaling pathway to induce cellular overgrowth, and show that Yki overexpression in the eye tissue of Drosophila results in compromised cardiac function. We rescue these cardiac phenotypes using antioxidant treatment, with which we conclude that the Yki induced tumorigenesis causes a systemic increase in ROS affecting cardiac function. Our results show that systemic cardiac dysfunction occurs due to abnormal cellular overgrowth or cancer elsewhere in the body; identification of specific cardiac defects associated with oncogenic pathways can facilitate the possible early diagnosis of cardiac dysfunction.